Articulación de resistencias a la expansión forestal en Uruguay y Argentina - Ramirez, Delia Concepción; Santos, Carlos (Pontificia Universidad Católica del Perú, 2024)
Piray 18 in Misiones (Argentina) and Paso Centurión in Cerro Largo (Uruguay) represent significant experiences of populations that managed to stop the advance of forestry. At the regional level, it has influenced the consolidation of foreign ownership and concentration of land ownership. The contexts also converge: these are areas considered productively marginal, on national borders (with Brazil and Paraguay), where hybrid forms of the national language (Spanish) coexist with subaltern languages (Jopará and Portuñol). The investigation of the subaltern politicization of local actors allows a different view of the hegemonic processes of economic, social and territorial transformation, based on the challenge to the development model installed in the policies of business promotion. The right to inhabit the territories and to a healthy environment is re-signified from these collective experiences and what we call environmental narrative is presented as a strategic resource of the actors in conflict to position themselves in opposition to forest agribusiness and to carry out strategic actions accordingly.

Piray 18 en Misiones (Argentina) y Paso Centurión en Cerro Largo (Uruguay) representan experiencias significativas de poblaciones que lograron detener el avance de la forestación, actividad que a nivel regional ha influido en la consolidación de la extranjerización y concentración de la propiedad de la tierra. Los contextos encuentran convergencias: se trata de áreas consideradas productivamente marginales, en fronteras nacionales (con Brasil y Paraguay), donde conviven formas híbridas de la lengua nacional (el castellano) con lenguas subalternas (el jopará y el portuñol). La indagación de la politicidad subalterna de los actores locales permite una mirada diferente sobre los procesos hegemónicos de transformación económica, social y territorial, a partir de la impugnación del modelo de desarrollo vinculado a las políticas de promoción empresarial. El derecho de habitar los territorios y acceder a un ambiente sano se ve resignificado a partir de estas experiencias colectivas. Lo que denominamos narrativa ambiental se presenta como un recurso estratégico de los actores en pugna para posicionarse en oposición al agronegocio forestal y llevar a cabo acciones estratégicas en consecuencia.
Articulation of Resistance to Forestry Expansion in Uruguay and Argentina
Keywords: Subaltern politics; Environmentalization; Resistance; Forest agribusiness; Politicidad subalterna; Ambientalización; Resistencias; Agronegocio forestal; https://purl.org/pe-repo/ocde/ford#5.04.00